(untitled) (Perner’s Contacts, 2006)
A successful public transport system must be based upon the needs of those who use and operate it. To be more successful, it must attract more new users, and satisfy theirs requirements. In the article there are opportunities for improvement of quality public transport. Its objective is to give similar or equal comfort and standard as the private means of transport.To compete with private transportation, public transport users should be able to perceive comfort dutiny their journey, even though they have to transfer from one mode or service to another.